Studies on the Mangroves of India 1. East Godavari Region - Sidhu, S. S. (Indian Forester, 1963)
The importance of the study of mangroves as brought out in the proceedings of the Mangrove Symposium (1957) has been stressed in the light of the previous and present work. The origin of the mangrove habitat and the world distribution of different species is dealt with. It is interesting to note that no species is continuously -disttibuted over both the hemispheres. The climate and geological data on the E. Godavari is summarized and tbe quantitative ecological data along with the description of the different communities is given. Scyphiphora hydrophyllacea a new record for this area is reported. Excoecaria agallocha is deciduous and not eve.,green. Various stages in the succession of the mangrove communities and factors operating in their development are discussed.